KEBINEKAAN MELAYU STUDI MELAYU SAMBAS DALAM LINTASAN SEJARAH DAN BUDAYA - Sunandar Sunandar; Tomi Tomi; Lamazi Lamazi (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2021)
Sambas society has been shaped over a long history. Several folklores serve as the foothold in interpreting and referring to the dynamics of the past. This paper contains two popular stories, namely Sambas from the eternal friendship between Syamsudin and Saribas, and Sambas which is interpreted as three ethnic groups. The two stories became the basis for seeing the diverse Sambas. To reveal the diversity of Malay Sambas, the research was carried out in four stages of the historical method, namely heuristics, verification, interpretation, and historiography. This study shows that the diversity in Sambas is recorded in the people’s collective memory, which aims to unite existing individuals.